Hormetic mechanism of sulfonamides on Aliivibrio fischeri luminescence based on a bacterial cell-cell communication. (January 2019) - Yao, Zhifeng; Wang, Dali; Wu, Xiaodan; Lin, Zhifen; Long, Xi; Liu, Ying
Abstract: Hormesis is a biphasic dose-response model with low-dose stimulation and high-dose inhibition. The mechanism for hormesis remains inconclusive, although it is becoming a central concept in toxicology. In this paper, the hormetic mechanism of sulfachloropyridazine (SCP) on Aliivibrio fischeri ( A. fischeri ) luminescence was explored by investigating into the interference of SCP with the bacterial quorum sensing (QS) communications. It was revealed that the SCP-induced hormesis on luminescence was due to its action on LitR – a key protein that connects lux and ain QS communications in A. fischeri . It was suggested SCP acted on LitR proteins to change its active forms, which subsequently induced hormetic effects on luxR (QS signal receptor) and thereby the luminescence. It is the first time that the hormetic mechanism based on bacterial QS was proposed, which provides a novel insight into the essence of the hormesis on A. fischeri luminescence. Highlights: Sulfonamides present time-dependent hormetic effects on bioluminescence. Sulfonamides act on bacterial quorum sensing communication to evoke hormesis. LitR protein in quorum sensing system has two active forms.